Maternal inhibition of infant behavioral response following isolation in novel surroundings and inflammatory challenge. Issue 4 (9th May 2012) - Hennessy, Michael B.; Jacobs, Sarah; Schiml, Patricia A.; Hawk, Kiel; Stafford, Nathan; Deak, Terrence
Abstract During isolation in a novel environment, guinea pig pups gradually begin to display passive behavior that appears to be mediated by proinflammatory activity, that is, "sickness behavior.". Administration of substances that increase proinflammatory activity [corticotropin‐releasing factor (CRF), lipopolysaccharide (LPS)] prior to isolation induces passive behavior from the beginning of the isolation episode. Here, we show that reunion with the mother in the novel environment rapidly and potently suppresses the passive behavior of isolated pups (Experiment 1); inhibits the passive behavior of pups administered CRF (10 µg, subcutaneous; Experiment 2); and inhibits the passive behavior of male, though not female, pups administered LPS (250 µg/kg, intraperitoneal; Experiment 3). Together these findings suggest that the presence of the mother either recruits other processes that moderate the impact of proinflammatory processes on brain mechanisms mediating the passive response or initiates compensatory mechanisms that counter the effect of proinflammatory activity. Further, the results suggest that for physically ill animals of social species, the adaptive advantage that accrues from maintaining normal social interactions may sometimes outweigh the advantage gained by engaging in sickness behavior. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 395–403, 2013